A new edible species of Lactifluus (Russulaceae) from Shorea robusta dominated forests in tropical India - Ghosh, Aniket; Bera, Ishika; Chakraborty, Dyutiparna; Hembrom, Manoj E.; Verbeken, Annemieke; Das, Kanad (Phytotaxa, 2022)
Macrofungal explorations undertaken to several Sal (Shorea robusta) dominated tropical forests of West Bengal and Jharkhand (India) yielded various wild mushrooms. Studies on these collections revealed an interesting and novel taxon of Lactifluus subg. Lactariopsis which is proposed herein as Lactifluus tropicalis. The new species is presented with both morphological and molecular data and is most closely related to L. leoninus, a species described from Papua New Guinea.